2002
DOI: 10.2134/jeq2002.1676
|View full text |Cite
|
Sign up to set email alerts
|

Basal Area Growth of Sugar Maple in Relation to Acid Deposition, Stand Health, and Soil Nutrients

Abstract: Previous studies have shown in noncalcareous soils that acid deposition may have increased soil leaching of basic cations above the input rate from soil weathering and atmospheric depositions. This phenomenon may have increased soil acidity levels, and, as a consequence, may have reduced the availability of these essential nutrients for forest growth. Fourteen plots of the Forest Ecosystem Research and Monitoring Network in Québec were used to examine the relation between post-industrial growth trends of sugar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
142
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(152 citation statements)
references
References 47 publications
8
142
2
Order By: Relevance
“…In our study, F. sylvatica maintains steady mean mature BAI at the HFL and CFA, comparable with mature tree AVI in P. rubens in the study reported by LeBlanc et al (1992). However, in many species BAI continues to increase with age in mature trees (Phipps & Whiton, 1988;LeBlanc, 1990a, b;Duchesne et al, 2002Duchesne et al, , 2003Fekedulegn et al, 2003;Muzika et al, 2004) in some cases showing no evidence of the reduction in slope that LeBlanc (1990a, b) associates with canopy closure.…”
Section: Temporal Trends In Baisupporting
confidence: 85%
See 1 more Smart Citation
“…In our study, F. sylvatica maintains steady mean mature BAI at the HFL and CFA, comparable with mature tree AVI in P. rubens in the study reported by LeBlanc et al (1992). However, in many species BAI continues to increase with age in mature trees (Phipps & Whiton, 1988;LeBlanc, 1990a, b;Duchesne et al, 2002Duchesne et al, , 2003Fekedulegn et al, 2003;Muzika et al, 2004) in some cases showing no evidence of the reduction in slope that LeBlanc (1990a, b) associates with canopy closure.…”
Section: Temporal Trends In Baisupporting
confidence: 85%
“…BAI series for dominant and codominant trees in mature stands typically show a period of early growth suppression (suppression phase) before a rapid increase in annual basal area growth (release phase). BAI may continue to increase in mature healthy mature trees (Phipps & Whiton, 1988;LeBlanc, 1990a, b;Duchesne et al, 2002Duchesne et al, , 2003Fekedulegn et al, 2003;Muzika et al, 2004), or stabilize (LeBlanc et al, 1992), but it does not show a decreasing trend until trees begin to senesce (LeBlanc, 1990a;Duchesne et al, 2002Duchesne et al, , 2003. During the suppression and release phases, growth is strongly affected by variation in light levels and is thus not easily compared between trees.…”
Section: Study Sites and Sample Preparationmentioning
confidence: 99%
“…The area of concern for sugar maples is based on study sites in north central Pennsylvania (LYNCH et al 2000) and regional studies (MITCHELL et al 1994). Forest soil acidification effects have also been reported in Ontario (WATMOUGH 2002;WATMOUGH, DILLON 2003) and Quebec (DUCHESNE et al 2002;PEART et al 1992), Canada. The Valley of Mexico area shown is located within the Mexico City Air Basin (FENN et al 2002) sites significantly improved sugar maple survival, crown vigor, tree growth, and seed production, whereas, black cherry and American beech were unaffected by the treatment (LONG et al 1997).…”
Section: Hardwood Forests Of the Midwest And The Northeastmentioning
confidence: 99%
“…Resampling of forest soils in northwestern Pennsylvania shows an increase in soil acidity of 0.78 and 0.23 pH units in the O and A horizons after 36 years (DROHAN, SHARPE 1997). The high mortality rates and reduced vigor reported for sugar maples experienced in northern Pennsylvania and Quebec, Canada over the last decade has been linked to cation depletion from those soils (DUCHESNE et al 2002;LONG et al 1997;HORSLEY et al 2000;MOORE et al 2000;DROHAN et al 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation